Web-Based Company Enquiry System / Ong Yook Hong - Ong, Yook Hong (2004)
Nowadays, information technology has pervaded into almost every industry in the country. Business organization today are moving to computerized their current systems to ensure smoother operations in the daily running of the business. Web-based company Enquiry System is proposed as to give a new impulse for my organization to gain more competitive advantages. The waterfall with Prototyping Model has been chose as the methodology of system development to develope the proposed system. Besides, the waterfall with prototyping model, a survey was carried out to gather more information. This system was used JSP as web programming language, IBM DB2 as the database and iPlanet Fast Track Edition 4.1 as the web server. This system consists of two section module. The two sections are customers section and administration section. The customers section will enable the customers to registered and login. The administration section enables the administrator to view the status and generating reports. Web-based Company Enquiry System is an online enquiry system for the small industries and services business, which is developed with the purpose to gain more competitive advantages and reduce the problem such as losing documentation and unable corresponding situation that currently facing by using manual system.